the The tripartite mechanism linking information security and digital forensic analysis: Digital forensics (Journal of Hama University, 2025)
In the light of the rapid growth in the world of technology, which has become linked to all spheres of life, the protection of information from theft has become one of the most important topics for large enterprises and companies because of the enormous amounts that can be lost if their systems are hacked. The digital forensic analyst also relies heavily on the information he can collect from these systems to detect the hacker.For this reason, in this research, we devised a mechanism to protect information and facilitate the work of the digital forensic analyst in detecting those trying to penetrate the system and steal information.The results obtained show the efficiency of the mechanism, as it is robust to resist attacks, attacker detection, and information protection.